2017
DOI: 10.21037/jtd.2017.03.75
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid technique for localization of subcentimeter lung nodules

Abstract: Background: It is technically challenging to locate non-visible, non-palpable subcentimeter ground-glass nodules (GGNs) of lung during video-assisted thoracic surgery (VATS). Computed tomography (CT)-guided marking of small pulmonary nodules using microcoils has been reported to be a practical method of preoperative localization, whereas dislodgement of microcoils remains to be a bothersome complication. The objective of this study was to assess the viability and effectiveness of a newly developed hybrid techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Accurate and effective preoperative or intraoperative localization techniques are helpful for successful wedge resection using VATS. Different materials have been used for the preoperative localization of SPNs [ 11 12 13 14 15 16 17 18 19 ]. Microcoils are relatively ideal for preoperative localization of SPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and effective preoperative or intraoperative localization techniques are helpful for successful wedge resection using VATS. Different materials have been used for the preoperative localization of SPNs [ 11 12 13 14 15 16 17 18 19 ]. Microcoils are relatively ideal for preoperative localization of SPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Only minor complications, i.e., a small pneumothorax and hemorrhage in the lung parenchyma, were detected on CT images. Several recent studies indicated that localization performed on the same day of surgery within a hybrid theatre is more safe and feasible (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative computed tomography-guided pulmonary nodule localization augmented by laser angle guide assembly operative localizations that render the nodules 'visible', which many studies have attempted to oblige (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Original Articlementioning
confidence: 99%